The role of LuxS in metabolism and signalling in Helicobacter pylori - Shen, Feifei (2010)
In many bacteria, LuxS functions as a quorum sensing (QS) molecule synthase. Its product, auto-inducer-2 (AI-2) plays a role in regulation of various bacterial activities in concert with cell population density. LuxS also has a second more central metabolic function in the activated methyl cycle (AMC) which generates the Sadenosylmethionine (SAM) required by methyltransferases and recycles the product via methionine. Helicobacter pylori lacks an enzyme catalysing homocysteine to methionine conversion, rendering the AMC incomplete and thus making any metabolic role of LuxSHp uncertain. Consequently, the mechanism underlying phenotypic changes upon luxS inactivation is not always clear. The aims of this project were to define the metabolic role of LuxS in H. pylori; to assess whether LuxSHp effects on bacterial motility were through metabolic effects or via production of the signalling molecule AI-2; and to explore the mechanism underlying motility phenotypic changes upon luxSHp inactivation. luxSHp is located next to genes annotated as cysKHp and metBHp, which are involved in cysteine and methionine metabolism in other bacteria. This study showed that isogenic mutants in luxSHp, cysKHp and metBHp could not grow without added cysteine (whereas wild-type could), suggesting roles in cysteine synthesis. Together with data from metabolite analyses, it confirmed that cysK-metB-luxS encode the capacity to generate cysteine from products of the incomplete AMC of H. pylori in a process of reverse transsulphuration. Consequently, the misnamed genes cysKHp and metBHp were recommended to be renamed mccAHp (methionine-to-cysteine-conversion gene A) and mccBHp, respectively. Data presented in this thesis also showed that disruption of luxS in H. pylori renders it non-motile, whereas disruption of mccA or mccB does not, implying that the loss of phenotype is not due to disruption of cysteine provision. The motility defect of the ΔluxSHp mutant could be genetically complemented with luxSHp and also by addition of in vitro synthesised AI-2, but not by addition of cysteine. Microscopy and immunoblotting further revealed that the motility defect of the ΔluxSHp mutant likely resulted from a reduction in the number and length of flagella due to loss of AI-2. This is supported by data obtained from quantitative RT-PCR (qRT-PCR). In conclusion, this study looked into the metabolic capacity of a three-gene cluster in H. pylori, including luxS. It showed that LuxSHp has a previously undescribed metabolic function in a cysteine provision pathway through a process of reverse transsulphuration. It also defined the precise steps in this pathway, and re-defined the roles of and renamed the two previously misnamed genes in the luxSHp cluster. It then addressed the controversial topic of the role of LuxS in bacteria: apart from being a central metabolic enzyme, is it a QS signalling molecule synthase? This study distinguished between the mechanisms underlying the alteration in motility of H. pylori ΔluxS mutants, and clarified whether this originated from a disruption of cysteine metabolism or signalling. Results showed that LuxS and its product, AI-2, influence motility via regulating flagellar gene transcription, suggesting the existence of an additional role for LuxS in H. pylori as a signalling molecule synthase.